Pelatihan Berpikir Desain dan Teknologi Digital dalam Implementasi Merdeka Belajar di SDN 105300 Deli Tua Sumatera Utara - Natalia Lusianingsih Sumanto; Albert Sembiring (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2023)
This community service aims to increase SD Negeri 105300 Deli Tua teachers' knowledge and skills in designing varied, interesting, differentiated learning processes and following the demands of the times through the application of design thinking and skills in digital technology. The method of implementing this service used ongoing training and assistance in making learning media with digital technology. The evaluation instrument used was a questionnaire, and it was analyzed descriptively. The results of this service showed that the teacher's knowledge and ability to design meaningful learning using digitalization technology according to the class phase increased significantly. Teachers had a growth mindset so that they became lifelong learning individuals and were adaptive in organizing digital-based learning and projects in their respective classes. On the other hand, the impact of this activity was felt by the participants as an increase in their sense of empathy for students.